1994
DOI: 10.3168/jds.s0022-0302(94)77207-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Test Day Measures for Somatic Cell Count, Milk Yield, and Protein Percentage of Milking Ewes

Abstract: Records from monthly test days for milk yield, natural log-transformed SCC, and protein percentage of 10,171 records of 3832 Spanish Churra ewes in 24 herds were analyzed to estimate genetic parameters. Heritabilities and genetic and phenotypic correlations for test day records were estimated using multivariate REML with an animal model, accounting for the effects of litter size, test day within herd group, age at lambing, and month in milk. Heritabilities for test day records of milk, log SCC, and protein per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
44
5
13

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 27 publications
12
44
5
13
Order By: Relevance
“…Ninane et al [11] verified the independence of their conversion for SCC at typical levels of somatic cells in raw cow's milk. However, somatic cells are naturally higher in raw sheep's milk there [2] (Tab. IV) and they might, in counts ≥ 1 000 000 SCC·mL -1 , have an effect on the enumeration of bacterial cells by BSC-FC [16].…”
Section: Methods Describing Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Ninane et al [11] verified the independence of their conversion for SCC at typical levels of somatic cells in raw cow's milk. However, somatic cells are naturally higher in raw sheep's milk there [2] (Tab. IV) and they might, in counts ≥ 1 000 000 SCC·mL -1 , have an effect on the enumeration of bacterial cells by BSC-FC [16].…”
Section: Methods Describing Criteriamentioning
confidence: 99%
“…Therefore, raw sheep's milk was examined here. Its biological, physical and chemical properties differ from raw cow's milk [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Heritability estimates, based on repeatability test-day models, range from 0.04 to 0.16 for several breeds including the Churra (Baro et al, 1994;El-Saied et al, 1998;Othmane et al, 2002), the Manchega (Serrano et al, 2003), the East Friesian (Hamann et al, 2004) and the Valle del Belice sheep breeds (Riggio et al, 2007). Other studies reported similar or slightly higher heritability estimates (from 0.11 to 0.18) for the average SCS during lactation, for Chios (Mavrogenis et al, 1999), Lacaune (Barillet et al, 2001;Rupp et al, 2003a), Latxa (Legarra and Ugarte, 2005) and Manech Red Faced ewes (Barillet et al, 2008).…”
Section: Genetic Parameters Of Scc and Mastitis In Sheepmentioning
confidence: 99%
“…Published genetic correlations between SCS and milk yield range from positive, i.e. antagonistic, to negative (Baro et al, 1994;El-Saied et al, 1998, 1999Barillet et al, 2001;Rupp et al, 2003a;Riggio et al, 2007).…”
Section: Genetic Correlations Between Scs and Other Traitsmentioning
confidence: 99%
“…Nevertheless, in the context of bovine selection strategies aimed at reducing the incidence of mastitis, investigations have been performed to evaluate the genetic relationships between veterinary-treated mastitis, SCC and milk production. Heritability of mastitis is low (0.024) while the heritability of SCC is moderate (0.17) [1,2,5]. However, the genetic correlation between the two traits is strong (0.72), suggesting a similar genetic determinism part [51].…”
Section: Management Practicesmentioning
confidence: 99%